(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the current problems related to the quality of education in the process of introducing digital technologies into the modern education system. The impact of digitalization on the educational process, its pedagogical and psychological aspects, infrastructural shortcomings and ways to eliminate them are covered on a scientific and theoretical basis. Also, issues of increasing the efficiency of education through innovative approaches are revealed.